2011
DOI: 10.1097/mao.0b013e318204ac1b
|View full text |Cite
|
Sign up to set email alerts
|

Speech Development After Cochlear Implantation in Children From Bilingual Homes

Abstract: Advanced language skills including the learning of a second spoken language are possible for children with cochlear implant living in bilingual homes, but that is the exception rather than the rule. It seems that other factors, such as spoken German language skills of the parents, integration of the family, and compliance with the rehabilitation program, play an important role. Therefore, a special support for children with cochlear implants from bilingual homes is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
2
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 7 publications
2
26
2
1
Order By: Relevance
“…Prior to this study, some researchers found evidence for the benefits of supporting both spoken languages for bilingual children with HL (e.g., Bunta & Douglas, 2013; Guiberson, 2014), but other studies came to different conclusions in that focusing on the language of the majority and limiting home language input may be needed for children with HL exposed to two languages (e.g., Deriaz et al, 2014; Teschendorf et al, 2011). As Guiberson (2014) notes, when it comes to bilingual children with HL, it is not unusual to encounter “fear that bilingualism may splinter linguistic resources or result in linguistic confusion” (p. 87).…”
Section: Figurementioning
confidence: 93%
See 4 more Smart Citations
“…Prior to this study, some researchers found evidence for the benefits of supporting both spoken languages for bilingual children with HL (e.g., Bunta & Douglas, 2013; Guiberson, 2014), but other studies came to different conclusions in that focusing on the language of the majority and limiting home language input may be needed for children with HL exposed to two languages (e.g., Deriaz et al, 2014; Teschendorf et al, 2011). As Guiberson (2014) notes, when it comes to bilingual children with HL, it is not unusual to encounter “fear that bilingualism may splinter linguistic resources or result in linguistic confusion” (p. 87).…”
Section: Figurementioning
confidence: 93%
“…It has to be noted that the age of implantation was considerably higher for members of the bilingual group than for those of the monolingual one — a factor that is unequivocally correlated with poorer speech and language outcomes for all children, even those with a coordinated language in the home and majority culture. Furthermore, as noted with the Teschedorf et al (2011) study, there was no control for potential disparity in socio-economic status across the monolingual and bilingual groups, and bilingual children came from various first language backgrounds. Nonetheless, Deriaz et al (2014) emphasized that bilingual children needed intensive and good quality input in both languages and also encouraged parental involvement in rehabilitation efforts.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations